Defining the Scope of Public Engagement: Examining the "Right Not to Know" in Public Health Genomics. Issue 1 (2014) - Allen, Clarissa; Sénécal, Karine; Avard, Denise
Abstract : While the realm of bioethics has traditionally focused on the rights of the individual and held autonomy as a defining principle, public health ethics has at its core a commitment to the promotion of the common good. While these two domains may at times conflict, concepts arising in one may also be informative for concepts arising in the other. One example of this is the concept of a "right not to know." Recent debate suggests that just as there is a "right to know" information about one's genetic status, there is a parallel "right not to know" when it comes to genetic information that if communicated, could be detrimental to an individual's social or psychological well-being. As new genetic technologies continue to change the nature of genetic testing and screening, it is crucial that normative frameworks to guide and assess genetic public health initiatives be developed. In this context, the question of whether a "right not to know" may also be said to exist for populations on a public health level merits attention.